High performance liquid chromatographic analysis of erythromycin in serum and urine - Stubbs, Christopher (Rhodes University, Faculty of Pharmacy, Pharmacy, 1985)
Erythromycin, a macrolide antibiotic used mainly against gram-positive bacteria has been in clinical use since 1952 (1). Previous pharmacokinetic data published on this antibiotic have been derived predominantly from microbiological assay techniques. However, these techniques are relatively imprecise as well as being non-specific and extremely tedious to perform. A novel high performance liquid chromatographic analysis of erythromycin in human serum and urine using U.V. detection at 200 nm and/or electrochemical detection using both an amperometric and a coulometric electrochemical detector is presented. The method involves a solid phase extraction procedure followed by a simple phase separation step and chromatography on a reverse phase column. In order to select the optimum U.V. detector for this analysis, five "state of the art" detectors were compared in terms of their signal-to-noise ratios at U.V. wavelengths between 200 and 210 nm. A known metabolite des-N-methylerythromycin is readily detectable using U.V. detection, whilst another metabolite/degradation product anhydroerythromycin is not seen using U.V. detection but is readily observable using an electrochemical detector. The method has a limit of sensitivity of 0.25 Î¼g/mL and 1.00 Î¼g/mL in serum and urine respectively (U.V. detection) and is sufficiently sensitive to monitor serum and urine concentrations of erythromycin in man after administration of a single 500 mg erythromycin stearate tablet.,KMBT_363,Adobe Acrobat 9.53 Paper Capture Plug-in
Keywords: High performance liquid chromatography; Erythromycin; Erythromycin -- Pharmacokinetics; Chromatographic analysis